Purification and Identification of a Novel Complex Which Is Involved in Androgen Receptor-Dependent Transcription - Hosohata, Keiko (American Society for Microbiology, 2003)
The androgen receptor (AR) binds to and activates transcription of target genes in response to androgens. In an attempt to isolate cofactors capable of influencing AR transcriptional activity, we used an immunoprecipitation method and identified a 44-kDa protein, designated p44, as a new AR-interacting protein. p44 interacts with AR in the nucleus and with an androgen-regulated homeobox protein (NKX3.1) in the cytoplasm of LNCaP cells. Transient-transfection assays revealed that p44 enhances AR-, glucocorticoid receptor-, and progesterone receptor-dependent transcription but not estrogen receptor- or thyroid hormone receptor-dependent transcription. p44 was recruited onto the promoter of the prostate-specific antigen gene in the presence of the androgen in LNCaP cells. p44 exists as a multiprotein complex in the nuclei of HeLa cells. This complex, but not p44 alone, enhances AR-driven transcription in vitro in a cell-free transcriptional system and contains the protein arginine methyltransferase 5, which acts synergistically with p44 to enhance AR-driven gene expression in a methyltransferase-independent manner. Our data suggest a novel mechanism by which the protein arginine methyltransferase is involved in the control of AR-driven transcription. p44 expression is dramatically enhanced in prostate cancer tissue compared with adjacent benign prostate tissue.